A Model to Implement Standardized Virtual Care for Low Back Pain Amongst a Large Network of Providers in Urban and Rural Settings - Marcia Rebecca Correale; Leslie Jayne Soever; Yoga Raja Rampersaud (SAGE Publishing, 2022)
Prior to the COVID-19 pandemic, virtual care (VC) was not routinely offered for assessment of low back pain (LBP), a highly prevalent, disabling condition. COVID-19 related healthcare closures resulted in a rapid backlog of patients referred to a provincial interprofessional LBP program. Without management, these patients were at high risk of experiencing untoward outcomes. Virtual care became a logical option. However, many clinicians lacked experience and confidence with LBP virtual care (LBP-VC); and either were unfamiliar with, or did not have access to, requisite technology. Multi-stakeholder engagement was utilized to understand barriers, identify enablers, and ultimately promote VC for LBP. As a result of the multi-stakeholder engagement, the concept of a toolkit for LBP-VC, including clinical resources and guidelines, emerged. The toolkit contains preparatory steps for VC and a standardized approach to virtual LBP assessment. Key steps in the toolkit have potential applicability to other musculoskeletal populations.